Fabrication of ZnO/Graphene Nanocomposite by Ultrasonic Homogenization - Pfund, Jacob D (Proceedings of the Wisconsin Space Conference, 2018)
Indium tin oxide (ITO) is a commonly used material in the production of transparent conducting films. However, indium is toxic, environmentally unfriendly, and expensive. To remedy this issue, a new material must be developed which can serve as a replacement for ITO. This project utilized commercially available zinc oxide powder and graphene nanoplatelets to manufacture nanocomposite materials through ultrasonic homogenization. To investigate their physical properties, these nanocomposites were then subjected to UV-Vis spectroscopy, particle size analysis, scanning electron microscopy, and X-ray diffractometry. Results indicate that ZnO/Graphene nanocomposites have promising potential as an inexpensive and environmentally friendly transparent conductor.